Pendampingan dan Penguatan Kemampuan Kognitif Siswa Berkebutuhan Khusus di SLBN Kebayakan Aceh Tengah: Cognitive Intervention and Support Services for Students with Special Educational Needs at SLBN Kebayakan Aceh Tengah - Saputra, Edy; Harahap, Ahmad Yunus Mokoginta (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This service activity entitled